1985
DOI: 10.1302/0301-620x.67b5.4055871
|View full text |Cite
|
Sign up to set email alerts
|

Stress fractures in military recruits. A prospective study showing an unusually high incidence

Abstract: In a prospective study of 295 male Israeli military recruits a 31% incidence of stress fractures was found. Eighty per cent of the fractures were in the tibial or femoral shaft, while only 8% occurred in the tarsus and metatarsus. Sixty-nine per cent of the femoral stress fractures were asymptomatic, but only 8% of those in the tibia. Even asymptomatic stress fractures do, however, need to be treated. Possible explanations for the unusually high incidence of stress fractures in this study are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
149
0
9

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(162 citation statements)
references
References 0 publications
4
149
0
9
Order By: Relevance
“…A number of military studies have found maximum stress fracture rates during the first 3 weeks of military training, although there is some disagreement. [22][23][24][25][26][27] On the basis of these observations, many believed that a period of rest from vigorous weight-bearing activities during the early weeks of BMT will reduce stress fractures. 28 Jones 29 proposed an approach that would allow for periods of recovery through alternating days of running and marching, so that training effects would not be diminished and risk of injury would not increase.…”
Section: Introductionmentioning
confidence: 99%
“…A number of military studies have found maximum stress fracture rates during the first 3 weeks of military training, although there is some disagreement. [22][23][24][25][26][27] On the basis of these observations, many believed that a period of rest from vigorous weight-bearing activities during the early weeks of BMT will reduce stress fractures. 28 Jones 29 proposed an approach that would allow for periods of recovery through alternating days of running and marching, so that training effects would not be diminished and risk of injury would not increase.…”
Section: Introductionmentioning
confidence: 99%
“…10 Stress fractures were first described in the medical literature as March Fractures by Briethaupt in 1855 who found them in the metatarsals of the Prussian Army recruits. 11 There are no data available on SF amongst Indian women but there is a need for research in this direction as well due to induction of women in the defence forces. There are very few prospective studies on SF available in the literature.…”
mentioning
confidence: 99%
“…[10][11][12] These injuries are frustrating and debilitating, often incurring considerable time lost from exercising, rehearsal, or military training. 13,14 SFxs are characterized by incomplete fractures that develop as a result of repetitive loading on a bone rather than a single traumatic event. Some ''high risk'' SFx are prone to delayed healing or catastrophic propagation to complete fractures.…”
mentioning
confidence: 99%